Coexistence of magnetism and superconductivity in separate layers of the iron-based superconductor - Topping, C; Kirschner, F; Blundell, S; Baker, P; Woodruff, D; Schild, F; Sun, H; Clarke, S (American Physical Society, 2017)
The magnetic properties attributed to the hydroxide layer of Li1-xFex(OH)Fe1-ySe have been elucidated by the study of superconducting and nonsuperconducting members of this family of compounds. Both ac magnetometry and muon spin relaxation measurements of nonsuperconductors find a magnetic state existing below ≈10 K which exhibits slow relaxation of magnetization. This magnetic state is accompanied by a low-temperature heat capacity anomaly present in both superconducting and nonsuperconducting variants suggesting that the magnetism persists into the superconducting state. The estimated value of magnetic moment present within the hydroxide layer supports a picture of a glassy magnetic state, probably comprising clusters of iron ions of varying cluster sizes distributed within the lithium hydroxide layer.